OBLIGATIONS IN MANUFACTURING ENTERPRISES SPECIFIC TO INTERNAL AUDIT CHARACTERISTICS - Nomozov Ilhomjon Ziyodullo o‘g‘li (Research Parks Publishers, 2023)
This is it in the article work release in enterprises obligations internal audit to himself special from the features come came out without improvement according to Suggestions work developed.